OMMR: Co-registration toolbox of OPM-MEG and MRI - Cao, Fuzhi; An, Nan; Xu, Weinan; Wang, Wenli; Li, Wen; Wang, Chunhui; Yang, Yanfei; Xiang, Min; Gao, Yang; Ning, Xiaolin (Frontiers in Neuroscience, 2022)
Magnetoencephalography (MEG) based on optically pumped magnetometers (OPM-MEG) has shown better flexibility in sensor configuration compared with the conventional superconducting quantum interference devices-based MEG system while being better suited for all-age groups. However, this flexibility presents challenges for the co-registration of MEG and MRI, hindering adoption. This study presents a toolbox called OMMR, developed in Matlab, that facilitates the co-registration step for researchers and clinicians. OMMR integrates the co-registration methods of using the electromagnetic digitization system and two types of optical scanners (the structural-light and laser scanner). As the first open-source co-registration toolbox specifically for OPM-MEG, the toolbox aims to standardize the co-registration process and set the ground for future applications of OPM-MEG.